Efektivitas Dan Efisiensi Pengelolaan Keuangan Daerah Di Kabupaten Banggai: Effectiveness and Efficiency of Regional Financial Management in Banggai Regency - Lilis Safitri S. Towendo; Amir Buhang (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2019)
This study aims to determine the level of effectiveness and efficiency of Regional Finance in Banggai Regency in 2014-2018. The types of data used are the realization of Regional Original Revenue (PAD), the target of Regional Original Revenue (PAD), as well as data on costs incurred to obtain Regional Original Income (PAD). The data source used is secondary data and is analyzed using effectiveness analysis where if the calculation result is above 100% then it is said to be effective as well as regional financial efficiency in Banggai Regency if the calculation result is below 60% then the assessment is very efficient. Regional Original Income determined in Banggai Regency showed that in 2014 Banggai Regency achieved good financial performance, namely, 103.27% or reached very effective criteria. Regional Original Income (PAD) each year tends to be inefficient and less efficient, as in 2014 at 98.93%, in 2015 at 101.04%, in 2016, 2017, and 2018 respectively at 98.14%, 99.47%, and 99.27%. Thus, it can be concluded that the level of effectiveness of regional financial management in Banggai Regency is included in the good criteria while the level of regional financial efficiency fluctuated from 2014 - 2018.